Estimating daily climatologies for climate indices derived from climate model data and observations. Issue 7 (13th April 2015) - Mahlstein, Irina; Spirig, Christoph; Liniger, Mark A.; Appenzeller, Christof
Abstract Climate indices help to describe the past, present, and the future climate. They are usually closer related to possible impacts and are therefore more illustrative to users than simple climate means. Indices are often based on daily data series and thresholds. It is shown that the percentile‐based thresholds are sensitive to the method of computation, and so are the climatological daily mean and the daily standard deviation, which are used for bias corrections of daily climate model data. Sample size issues of either the observed reference period or the model data lead to uncertainties in these estimations. A large number of past ensemble seasonal forecasts, called hindcasts, is used to explore these sampling uncertainties and to compare two different approaches. Based on a perfect model approach it is shown that a fitting approach can improve substantially the estimates of daily climatologies of percentile‐based thresholds over land areas, as well as the mean and the variability. These improvements are relevant for bias removal in long‐range forecasts or predictions of climate indices based on percentile thresholds. But also for climate change studies, the method shows potential for use.